2022
DOI: 10.3389/fimmu.2022.752105
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor Triggers Lysosomal Leakage Through Calcium Mobilization in a Mechanism Dependent on Pannexin-1 Hemichannels

Abstract: The P2X7 receptor is a critical purinergic receptor in immune cells. Its activation was associated with cathepsin release into macrophage cytosol, suggesting its involvement in lysosomal membrane permeabilization (LMP) and leakage. Nevertheless, the mechanisms by which P2X7 receptor activation induces LMP and leakage are unclear. This study investigated cellular mechanisms associated with endosomal and lysosomal leakage triggered by P2X7 receptor activation. We found that ATP at 500 μM and 5 mM (but not 50 μM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…56−58 Rapidly dividing cancer cells are strongly dependent on effective lysosomal function, and dramatic changes in lysosomal volume, composition, and cellular distribution occur during cancer transformation and progression; these changes promote the invasive growth of tumors. 59 This makes cancer cells more sensitive to the impairment of lysosomes. Moreover, apoptosis-resistant cancer cells can still undergo lysosomal cell death.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56−58 Rapidly dividing cancer cells are strongly dependent on effective lysosomal function, and dramatic changes in lysosomal volume, composition, and cellular distribution occur during cancer transformation and progression; these changes promote the invasive growth of tumors. 59 This makes cancer cells more sensitive to the impairment of lysosomes. Moreover, apoptosis-resistant cancer cells can still undergo lysosomal cell death.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, apoptosis-resistant cancer cells can still undergo lysosomal cell death. 59 Thus, the targeting of lysosomes and induction of lysosome-dependent cell death represent promising therapeutic strategies for cancer treatment. 56 , 60 62 From this point of view, the Ir complexes described in this study offer exciting potential, mainly because the disintegration of lysosomes and subsequent cellular effects can be triggered explicitly by light at the tumor site.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous research has identified mast cells in the trachea and AMs in the alveoli as primary sources of CTSC [ 78 ]. Moreover, studies have indicated that several DAMPs including cholesterol crystals and ATP, could induce LMP in macrophages and lead to the release of lysosomal proteases [ 79 , 80 ]. In our study, we confirmed that extracellular histones, among these same DAMPs, induced LMP in AMs using various fluorescence staining methods.…”
Section: Discussionmentioning
confidence: 99%
“…This signal triggers reactive astrogliosis and recruits microglia and other peripheral immune cells, thereby increasing the susceptibility of neurons to damage [85]. Since Cx43 hemichannels and Panx1 channels facilitate the release of ATP in astrocytes [52,53], and considering that ATP activates these channels by increasing the influx of Ca 2+ via P2X7 receptors [86,87], we evaluated whether these receptors play a role in ethanolinduced channel activity. Blocking P2X7 receptors with 200 nM A740003 or 200 µM oxidized ATP (oATP) partially decreased ethanol-induced Etd uptake (Fig.…”
Section: Ethanol Induces the Release Of Atp And Glutamate Through Dif...mentioning
confidence: 99%